(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
Smelting reduction of spent lithium-ion batteries (LIBs) results in metallic alloys containing Co, Ni, Cu, Fe and Mn. Dissolution of the valuable metals present in the metallic alloys is necessary to recover them. In this work, the mixture of Fe2(SO4)3 and FeSO4, single Fe2(SO4) and FeCl3 solutions were employed as leaching agents and the leaching behaviour of the metals was investigated. The difference in the leaching percentage of the metals by the nature of the ferric solutions was insignificant. In these leaching systems, ferric and hydrogen ions act as oxidizing agents and sulfate/bisulfate and chloride anions as ligands. Optimum conditions for the complete leaching of metals by single ferric solutions were 0.35 mol/L Fe2(SO4)3 or 0.7 mol/L FeCl3 with 12.5 g/L pulp density for 60 min at 22oC. Addition of H2O2 to the leaching solution for the oxidation of Fe(II) to Fe(III) enhanced the selective extraction of iron over Co(II), Ni(II), Cu(II), Mn(II) and Si(IV) by D2EHPA. Stripping of iron from the loaded D2EHPA with aqua regia resulted in a pure iron solution. Compared to HCl and H2SO4 solutions, use of single ferric solution showed some advantages like fast reaction kinetics at 22oC and the reduction in dosage of acids and oxidizing agents.